The optical properties of Tm3＋ doped Na5Lu9F32 single crystal - 盛启国 夏海平 汤庆阳 何仕楠 章践立 陈宝玖 (Optoelectronics letters, 2017)
Tm（3＋） doped Na5Lu9F（32） single crystal with high optical quality was grown by an improved Bridgman method. The Judd-Ofelt intensity parameters Ωt（t=2, 4, 6） were calculated according to the measured absorption spectra and physical-chemical properties of the obtained Na5Lu9F（32） single crystal. The stimulated emission cross-section of the 3F4→3H6 transition（～1.8 μm） is 0.35×10（-20） cm2 for Tm（3＋） doped Na5Lu9F（32） single crystal. The emission spectra under the excitation of 790 nm laser diode（LD） and fluorescence lifetime at 1.8 μm were measured to reveal the fluorescence properties of Tm（3＋） doped Na5Lu9F（32） single crystal. The research results show that the Tm（3＋） doped Na5Lu9F（32） single crystal has larger stimulated emission cross-section compared with other crystals. All these spectral properties suggest that this kind of Tm（3＋）doped Na5Lu9F（32） crystal with high physical-chemical stability and high-efficiency emission at 1.8 μm may be used as potential laser materials for optical devices.